2023
DOI: 10.1136/bmjoq-2022-002124
|View full text |Cite
|
Sign up to set email alerts
|

Reducing incidence of postoperative acute kidney injury in trauma and orthopaedics patients: a quality improvement project

Abstract: BackgroundAcute kidney injury (AKI) is a common postoperative complication which increases morbidity and mortality. This quality improvement project aimed to implement measures targeting known risk factors to decrease the incidence of postoperative AKI in trauma and orthopaedics (T&O) patients.MethodsData were collected across three six-month to 7-month cycles between 2017 and 2020, analysing all elective and emergency T&O operated patients within a single NHS Trust (n=714, 1008 and 928, respectively).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Identifying and monitoring patients at increased risk may underpin strategies to improve outcomes. The value of targeting AKI in hip fracture patients has been recently demonstrated in an interventional study of withholding certain medications preoperatively in emergency and elective T&O patients ( 67 ). The investigators found a significant reduction in postoperative AKI ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Identifying and monitoring patients at increased risk may underpin strategies to improve outcomes. The value of targeting AKI in hip fracture patients has been recently demonstrated in an interventional study of withholding certain medications preoperatively in emergency and elective T&O patients ( 67 ). The investigators found a significant reduction in postoperative AKI ( 67 ).…”
Section: Discussionmentioning
confidence: 99%